The Future of Polish Labour Market and the Issue of Work Motivation in Older People - Łaszkiewicz, Edyta; Bojanowska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
According to the demographic forecasts, the population of people in their productive working age decreases, while the share of people aged 65 and over increases. The negative demographic tendencies will affect the conditions of labour market. If the workers’ activity rate doesn’t rise, the total number of workers will decrease dramatically. The demographical pressures on the labour market should result in a prolonging of people’s professional activity. The increase of the labour market activity seems to be one of the most important goals for Poland, for the coming years. One of the factors, which might help in maintaining the high rate of labour market activity (especially among those who are in the pre‑retirement age) is the adaptation of working conditions to the needs of people of various ages. The possibility of working remotely, the flexibility of weekly hours of work or the financial benefits might motivate younger and older workers in different ways. Hence, the use of mechanisms which support the economic activity of older people requires an identification of solutions which will benefit this group of workers the most. The aim of this research is the identification of age‑related differences in factors which motivate workers to continuing working activity. We used the database of individuals from Polish Social Diagnosis (for 2015) and applied the logit regression models to verify if there are age differences in the way people prefer to be motivated to work. We found that what motivates elderly workers doesn’t always motivate the others in the same way. Pre‑retirement age workers prefer, more than others, to be independent and to have a job which is related to their experience. The financial motivators as well as the stability of employment, although very important for all workers, seem to be less important for the elderly workers because they have achieved pension rights.